Republic of Belarus : Staff Report for the 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Belarus. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the economy of Belarus contracted by 3.9 percent in 2015, with a similar performance in the first half of 2016. The exchange rate depreciated sharply during 2015 and part of 2016. Real wages are down substantially relative to 2014, and corporate losses are up. Unemployment has risen somewhat, though it remains relatively low. The economy is expected to contract further in 2016 and in 2017, reflecting still-weak balance sheets and structural impediments. A subdued recovery is expected in 2018, but over the medium term, potential growth is expected to increase only to about 1.75 percent, limited by negative demographic developments and low productivity growth.